Effects of an agribusiness collapse on contract growers and their communities : a case study of Makeni Cooperative Society, Lusaka, Zambia - Mfune, Elizabeth (Rhodes University, Faculty of Humanities, Department of Sociology, 2006)
This study assesses the effects of an agribusiness collapse, on the contracted growers and their surrounding communities in Lusaka Province, Zambia. In 2004, Agriflora Limited, a Trans-Zambezi Industries Limited (TZI) agribusiness in Lusaka Zambia was sold off. Agriflora Limited was one ofthe largest fresh vegetable exporters in Africa. It had contracted almost 500 small-scale farmers with 1-4 hectares of land within 50 km radius of Lusaka to grow vegetables for export. Makeni Cooperative Society was one of the targeted groups of growers. It grew baby corn, mangetout peas, and sugar snap and fine beans for export. The case study relied on both primary and secondary data. I undertook two months of ethnographic fieldwork utilising observations, in-depth interviews and informal discussions with some community members in Makeni. I also reviewed the literature on contract farming schemes (documenting both the negative and positive effects for growers) in developing countries. The case study showed that the impact of the collapse of Agriflora on the growers has been severe indeed; there has been a significant reduction in production with only a few farmers producing for export. Those that are producing are limited to one crop, baby corn. The effect on the local labour market (farm workers) has been quite drastic with a drop in employment. A new agribusiness company, York Farm, was sourced by the government for the contract growers of Makeni. York Farm has signed a procurement contract under which only sale and purchase conditions are specified. This means that, services such as extension services are no longer provided. It was also found that despite the price for baby corn at York Farm being better than what Agriflora used to offer the farmers, farmers are not producing peas which have a higher turnover than baby corn because York farm does not buy peas from the farmers. However, the farmers are hopeful that they will soon start producing peas after they pass the Eurep gap requirements. Furthermore, the farmers are still interested in contract farming as they are convinced that it can lead to higher farm incomes. While the neoliberal critique of the pre- Structural Adjustment agricultural policies was based on the need to improve rural farming income and productivity, my study shows that the contract farmers are not the "traditional" peasant farmers but retired civil servants or former public sector employees who lost their jobs during the contraction of the sector. In conclusion, my field work revealed that the collapse of Agriflora has had negative effects on the growers of MCS in terms a significant decrease in crop production, decline in farmer income, lack of technical assistance such as extension services, transportation problems (to take produce to the new market-York Farm) and reduced contraction in employment opportunities for farm workers.
Keywords: Agriculture -- Economic aspects -- Zambia; Agricultural industries -- Zambia; Farmers -- Zambia -- Economic conditions; Cooperative societies -- Zambia; Contracts, Agricultural -- Zambia